Nestin Promotes Peritoneal Fibrosis by Protecting HIF1-α From Proteasomal Degradation - Shentu, Yangping; Jiang, Huanchang; Liu, Xiaoyuan; Chen, Hao; Yang, Dicheng; Zhang, Jinqi; Cheng, Chen; Zheng, Yulin; Zhang, Yang; Chen, Chaosheng; Zheng, Chenfei; Zhou, Ying (Frontiers in Physiology, 2020)
Background: Peritoneal dialysis (PD) is a treatment for end stage renal disease patients, but it can also cause peritoneal fibrosis. Nestin is known as a neural stem cell marker and it has many functions. The hypoxia induced factor (HIF) signaling pathway can be activated under hypoxia condition, leading to the overexpression of some angiogenesis related genes. The aim of our study is to demonstrate Nestin’s role in the development of peritoneal fibrosis (PF), and to provide a new target (Nestin) to treat PF. Methods: PD mice models were constructed by an intraperitoneal administration of PDS at 10 ml/100g/d for 4 weeks. Nestin-positive cells were isolated from peritonea of Nestin-GFP mice by flow cytometry. The relationship of Nestin and HIF1-α-VEGFA pathway was detected by Nestin knockdown, Coimmunoprecipitation and immunofluorescence. Also, proteasomal activity was demonstrated by CHX and MG132 application, followed by Western blotting and Coimmunoprecipitation. Results: In our experiments, we found that Nestin expression resulted in PF. Also, HIF1-α/VEGFA pathway was activated in PF. Nestin knockdown reduced the level of HIF1-α. Nestin directly bound to HIF1-α and protected HIF1-α from proteasomal degradation. Overexpression of HIF1-α reverts the fibrosis levels in Nestin-knockdown cells. In brief, Nestin inhibited the degradation of HIF1-α by mitigating its ubiquitination level, leading to the activation of HIF1-α signaling pathway, and eventually promoted PF. Conclusion: We found a novel mechanism of PF that Nestin promotes by protecting HIF1-α from proteasomal degradation. Taken together, our key findings highlight a novel mechanism which silencing of Nestin hinders HIF1- α -induced PF.